2007
DOI: 10.1007/s11199-007-9255-8
|View full text |Cite
|
Sign up to set email alerts
|

Eternal Mothers or Flexible Housewives? Middle-aged Chinese Married Women in Hong Kong

Abstract: How do Hong Kong Chinese women position themselves in relation to this stigmatized social category of "si-nai" (middle aged-housewives) and the prevailing norms and values regarding women's roles? The case of middleaged, married women in Hong Kong provides empirical support for an alternative understanding of the identity of adult woman and helps to problematize conceptualizations of women's identity as centered on their mother roles. The narratives of these twenty-six women show the fluidity of their roles as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…This finding might reflect a traditional gender stereotyped role that is still prevalent in Taiwan. Women, especially married ones, are expected to conform to the gender ideology of xiang fu jiao zi (supporting their husband and rearing sons; Ho, 2007). Thus, it is possible that a woman who perceives problems with one of these primary relationships might feel more anxious about "failing" in the other role.…”
Section: The Persistence Of Negative Emotionsmentioning
confidence: 99%
“…This finding might reflect a traditional gender stereotyped role that is still prevalent in Taiwan. Women, especially married ones, are expected to conform to the gender ideology of xiang fu jiao zi (supporting their husband and rearing sons; Ho, 2007). Thus, it is possible that a woman who perceives problems with one of these primary relationships might feel more anxious about "failing" in the other role.…”
Section: The Persistence Of Negative Emotionsmentioning
confidence: 99%
“…An interpretive approach was adopted to focus on how individuals constructed meaning out of the social interaction process (Charmaz, 2003) and the way in which their interpretations generated different responses to the situations (Ho, 2007). Open coding was conducted for both field notes from participant observation and the semistructured interview transcripts by examining the text line by line (Dahlgren, Emmelin, & Winkvist, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present study showed that the majority of mothers were working and the stressful work environments in Hong Kong may have added extra burden on the mothers (So, ). In addition to long hours at work, many women in contemporary Hong Kong society need to take care of household tasks (Ho, ). Although more husbands are willing to share domestic work with their wives, traditional values about gender roles in the household continue to construct the division of labor, and women still shoulder the major responsibility of domestic work (Ho, ).…”
Section: Discussionmentioning
confidence: 99%